Low-dose Norfloxacin-treated leptospires induce less IL-1β release in J774A.1 cells following discrepant leptospiral gene expression. (June 2018) - Cao, Yongguo; Xie, Xufeng; Zhang, Wenlong; Wu, Dianjun; Tu, Changchun
Abstract: Currently, accumulating evidence is challenging subtherapeutic therapy. Low-dose Norfloxacin (Nor) has been reported to suppress the immune response and worsen leptospirosis. In this study, we investigated the influence of low-dose Nor (0.03 μg/ml, 0.06 μg/ml, 0.125 μg/ml) on leptospiral gene expression and analyzed the immunomodulatory effects of low-dose Nor-treated leptospires in J774A.1 cells. To study the expression profiles of low-dose Nor-treated leptospires, we chose LipL71/LipL21 as reference genes determined by the geNorm applet in this experiment. The results showed that low-dose Nor up-regulated the expression of FlaB and inhibited the expression of 16S rRNA, LipL32, LipL41, Loa22, KdpA, and KdpB compared with the untreated leptospires. These results indicated that low-dose Nor could regulate leptospiral gene expression. Using RT-PCR, the gene expression of IL-1β and TNF-α in J774A.1 cells was detected. Nor-treated leptospires induced higher expression levels of both IL-1β and TNF-α. However, when analyzed by ELISA, the release of mature IL-1β was reduced compared with that observed in cells induced with no Nor-treated leptospires, although the TNF-α protein level showed no significant change. Our study indicated that the gene expression of leptospires could be modulated by low-dose Nor, which induced less IL-1β release in J774A.1 cells. Highlights: The reference genes of leptospira are not identical in different conditions. Low-dose norfloxacin promoted the expression of Flab, but inhibited the expression of others in leptospires. Low-dose norfloxacin-treated leptospires up-regulated the gene expression of IL-1β and TNF-α in J774A.1 cells. Low-dose norfloxacin-treated leptospires inhibited the IL-1β but TNF-α at protein level in J774A.1 cells.